Nuclear ubiquitin proteasome degradation affects WRKY45 function in the rice defense program. (8th November 2012) - Matsushita, Akane; Inoue, Haruhiko; Goto, Shingo; Nakayama, Akira; Sugano, Shoji; Hayashi, Nagao; Takatsuji, Hiroshi
Summary: The transcriptional activator WRKY45 plays a major role in the salicylic acid/benzothiadiazole‐induced defense program in rice. Here, we show that the nuclear ubiquitin–proteasome system (UPS) plays a role in regulating the function of WRKY45. Proteasome inhibitors induced accumulation of polyubiquitinated WRKY45 and transient up‐regulation of WRKY45 target genes in rice cells, suggesting that WRKY45 is constantly degraded by the UPS to suppress defense responses in the absence of defense signals. Mutational analysis of the nuclear localization signal indicated that UPS‐dependent WRKY45 degradation occurs in the nuclei. Interestingly, the transcriptional activity of WRKY45 after salicylic acid treatment was impaired by proteasome inhibition. The same C‐terminal region in WRKY45 was essential for both transcriptional activity and UPS‐dependent degradation. These results suggest that UPS regulation also plays a role in the transcriptional activity of WRKY45. It has been reported that AtNPR1, the central regulator of the salicylic acid pathway in Arabidopsis, is regulated by the UPS. We found that OsNPR1/NH1, the rice counterpart of NPR1, was not stabilized by proteasome inhibition under uninfected conditions. We discuss the differences in post‐translational regulation of salicylic acid pathway components between rice and Arabidopsis.